Vilas rurais: Espaço de ressignificação do ideário liberal - Fabris, Diuslene Rodrigues (2006)
The present study is concerned about aspects of State intervention while the manager of the social policies in the everyday life of families who lives in Salto São Francisco Rural Village, in West of Paraná, seeking to identify the way the liberal thought about property importance, freedom and family is reflected in the discourse and in the routine of these workers. For doing so, we make an evaluation of the State action impact on the context, taking into account the real perception from these residents about the interference made by professional knowledge and implemented by the institutional bodies. In this paper we consider that to understand the state action in the social relation scope, in the context of program in focus, is to take into account that the achievements of the social action cannot be measured only by the market value gaining, but it also implies to consider the extension of the results after the deed. For the research development we used some different tools for data collection, such as field report, semi-structural interviews, structural interviews, and documents consulting. The authors we have as theoretical basis were Hobbes (1997), Locke (1998), Dumont (1993). First we present some discussions about the concept that lies in the State liberal theory. Next, we presented and set the context of the coming up of social policies, as well as the family function that, along the history mediated the state action. In this perspective, authors as Engels (1984), Donzelot (1986), Neto (1996) and others contemporary ones, give the basis to the presupposed considerations. From the authors like Heredia (1979), Palmeiras (1977), Wanderley (2005), Brenneisen (1994) and Martins (2000), we present the issue about land in Brazil and the daily reality of the residents of Salto São Francisco Rural Village that, in the audience condition, take part in a social policy.